Evaluation of HIV-1 reservoir size and broadly neutralizing antibody susceptibility in acute antiretroviral therapy-treated individuals. (1st February 2022) - Moldt, Brian; Günthard, Huldrych F.; Workowski, Kimberly A.; Little, Susan J.; Eron, Joseph J.; Overton, Edgar T.; Lehmann, Clara; Rokx, Casper; Kozal, Michael J.; Gandhi, Rajesh T.; Braun, Dominique L.; Parvangada, Aiyappa; et al.
Abstract : Objective: Persistence of the viral reservoir is the main barrier to curing HIV. Initiation of ART during acute HIV infection can limit the size and diversity of the reservoir. In depth characterization of the reservoir in individuals who initiate ART during acute infection will be critical for clinical trial design and cure strategies. Methods: Four cohorts with participants who initiated ART during acute infection or during chronic infection were enrolled in a cross-sectional, noninterventional study. Viral reservoir was evaluated by the Intact Proviral DNA Assay (IPDA), the Total HIV DNA Assay (THDA) and the Quantitative Viral Outgrowth Assay (QVOA). Viral diversity and susceptibility to V3-glycan bNAbs were determined by genotyping of the viral envelope gene. Results: Participants who initiated ART during the acute Fiebig I–IV stages had lower level of total HIV DNA than participants who initiated ART during chronic infection whereas no difference was observed in intact HIV DNA or outgrowth virus. Participants who initiated ART during Fiebig I–IV also had lower viral diversity and appeared to have higher susceptibility to bNAbs than participants initiating ART during chronic infection. Conclusion: Individuals initiating ART during Fiebig I–IV had small viral reservoirs, low viral diversity, and high susceptibility to bNAbs, and would be an optimal target population for proof-of-concept HIV cure trials. Abstract : Supplemental Digital Content is available in the text